1997
DOI: 10.1021/bi9613483
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression of a Type IV, cAMP-Specific Phosphodiesterase:  Characterization and Structure−Function Studies of Deletion Mutants

Abstract: A potential role for cAMP in regulating the differentiation of myoblasts has led us to examine the components of the cAMP signaling system, including the type IV, cAMP-specific phosphodiesterases. The full coding sequence of the phosphodiesterase PDE4D1 was inserted in the bacterial expression vector pGEX-KG. N- and C-terminal truncations were also placed in the same vector, allowing the expression and purification of glutathione S-transferase (GST)-PDE fusion proteins using glutathione-Sepharose. The purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 47 publications
(74 reference statements)
4
23
0
1
Order By: Relevance
“…8A). Such an increase in PDE activity following deletion and/or mutation of the N terminus has been previously reported for PDE3 and PDE4 (24,25,43). Despite the dramatic increase in PDE activity, this mutant failed to enhance the production of IL-2 in response to SEE and APCs (Fig.…”
Section: Expression Of Functional Pde4b2-gfp In Jurkat T Cellssupporting
confidence: 78%
“…8A). Such an increase in PDE activity following deletion and/or mutation of the N terminus has been previously reported for PDE3 and PDE4 (24,25,43). Despite the dramatic increase in PDE activity, this mutant failed to enhance the production of IL-2 in response to SEE and APCs (Fig.…”
Section: Expression Of Functional Pde4b2-gfp In Jurkat T Cellssupporting
confidence: 78%
“…Another study with PDE3 showed similar K m values with amino-terminal deletion mutants, but the V max values increased with larger amino-terminal deletions (40). Similarly, several studies involving PDE4 amino-terminal deletion mutants determined that these enzymes had similar K m values as did wild type PDE4, but increased specific enzyme activity (15,42). These results reveal a similar pattern of properties shared by PDE catalytic domains, and support the notion that results from our studies with PDE5 catalytic fragment may apply to those of other mammalian PDEs.…”
supporting
confidence: 85%
“…In the presence of UCR1, ERK phosphorylation leads to suppression of PDE4D catalytic activity; whereas in the absence of UCR1, the functional consequence of this modification is activation (22)(23)(24). On the other hand, UCR2 bears an autoinhibitory property against PDE4D catalytic activity (25)(26)(27). Given that ERK hyperactivation is common across human cancers, loss of UCR1/UCR2 caused by the genomic microdeletions will conceivably lead to PDE4D activation.…”
Section: Discussionmentioning
confidence: 99%